Noise Pollution in Biochemistry Laboratories of Different Hospitals in Istanbul/Turkey - Erdoğan Gültekin; Murat Yener; Ömer Necati Develioğlu; Hakan Köleli; Mehmet Külekci (Turkish Archives of Otorhinolaryngology, 2013)

(untitled)
Objective:To measure and analyse noise levels generated by different biochemistry analysers in public hospitals.Methods:Noise levels generated from different analysers were measured in biochemistry laboratories by using a sound level meter. Each device was operated separately and noise levels were measured for 15 minutes; the lowest and highest sound pressure levels were recorded and compared with the World Health Organisation (WHO) guidelines for community noise. Also, 20 laboratory workers were chosen randomly and their hearing levels were screened.Results:The highest noise level recorded from biochemical analysers was 81 dB with an average of 77.7±2.11 dB; the lowest noise level was 64 dB with an average of 66.9±1.66 dB. The average highest noise level of total blood count devices was 78.5±5.94 dB and the average lowest noise level was 66.3±7.05 dB. The average highest measurement of hormone analysers was 78.5±1.95 dB and the average lowest measurement was 66.1±4.53 dB. The average highest measurement of urine analysers was 75.3±5.39 dB and the average lowest measurement was 64.3±4.62 dB. The average highest noise level of centrifuge devices was 80.6±5.68 dB and the average lowest noise level was 69.2±5.75 dB. In the audiometric screening, the hearing thresholds were within normal levels.Conclusion:The WHO guidelines state that noise levels in hospital areas should be 35-40 dB in the daytime and 30-40 dB in the evening. Our results exceed these guidelines at all times.